2015
DOI: 10.1159/000370003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Maternal Bile Acid Quantification in Intrahepatic Cholestasis of Pregnancy as an Adverse Perinatal Outcome Predictor

Abstract: Aims: To evaluate the correlation between perinatal outcome and bile acid levels in intrahepatic cholestasis of pregnancy (ICP), and to evaluate variations in the mean bile acid level when stratifying by maternal and perinatal factors. A comparison between mild and severe ICP was made. Methods: A prospective observational study was performed in pregnant patients who underwent blood tests for bile acids due to persistent pruritus. Based on bile acid levels, maternal and neonatal data were obtained and were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Maternal outcomes are excellent, however, there is a risk of fetal distress, preterm labor, prematurity, and intrauterine death (41)(42)(43)(44)(45). Early delivery at 37 weeks is encouraged, because intrauterine death is more common in the last month of pregnancy and few deaths occur before 37 weeks ( 46 ).…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…Maternal outcomes are excellent, however, there is a risk of fetal distress, preterm labor, prematurity, and intrauterine death (41)(42)(43)(44)(45). Early delivery at 37 weeks is encouraged, because intrauterine death is more common in the last month of pregnancy and few deaths occur before 37 weeks ( 46 ).…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…The derivation of the relevant studies included in the present meta‐analysis is shown in Figure . Of the 368 publications initially found in PubMed, nine involving about 1928 patients were included in this meta‐analysis . The major characteristics of the nine eligible publications are described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were designed as prospective case–control studies six studies were retrospective observational studies; and one study was a prospective cohort study . Three studies were conducted in Europe three in the USA; and three in Asia . Sub‐group analysis was performed with stratification by region and study design (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Present results were also contrary to those of Glantz A et al who conducted a meta-analysis and found that maternal elevated bile acid levels are significantly associated with increased risks of overall adverse perinatal outcomes, PTB, MSAF, and asphyxia or RDS. 13,14 The earlier gestational age at delivery, particularly an increase in the number of iatrogenic preterm deliveries could be explained by the fact that patients were managed actively during pregnancy after an established diagnosis of ICP.…”
Section: Discussionmentioning
confidence: 99%